Noise Level Assessment Near the Hospitals Located in Dhangadhi Sub-Metropolitan City - Pant, Prakash Raj; Dhungana, Sandesh; Joshi, Prem Raj; Saud, Prem Singh (Journal of Durgalaxmi, 2024)
Undesirable sound is called noise. Excessive amounts of sound in the environment causes noise pollution. Noise pollution is one of the major environmental problems in recent times especially in urban regions. This study aims to examine the noise levels near hospitals located in Dhangadhi Sub-Metropolitan City. A total of nine hospitals were selected for this study which are located in Dhangadhi Sub-Metropolitan City. The noise level was recorded in those hospitals in morning (8:00-10:00), day (14:00-16:00) and evening (17:00- 19:00) time. A digital sound meter was used to measure noise levels in the month of February 2024. This study showed that noise levels (Leq) at those hospitals were more than the prescribed noise level. In the selected hospitals higher noise levels was observed in those hospitals which are near the roads or highways. Less noise level was measured in the hospitals which are inside the road. This study Concluded that the high traffic of vehicles on the road, bad condition of the road, human crowds, and unnecessary use of horns are the major causes of noise pollution in those hospitals.